Integration of Cash Waqf in the Halal Value Chain Ecosystem: A Strategy to Strengthen the Competitiveness of Halal Products Based on Sharia Economics - Izzun Khoirun Nissa; Yuni Safitri; Galuh Anisa Fala (Penerbit USIM, 2025)
International Halal Management Conference (IHMC) : “Empowering Halal Industry Towards Globalization” / Editor :-Farah Laili Muda @ Ismail, Nur Ainna Ramli & Anita Ismail Organized by Faculty of Economics & Muamalat, Universiti Sains Islam Malaysia 9 September 2025